Relationship of Hot Work Climate with Employee Blood Pressure in Binat Installation, Dr. Sardjito - Charles Kimura1,Ledita Sartika Goddess2, Zikri Fathur Rahman1, Abdul Rohim Tualeka1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Blood pressure in each individual varies, and depends on age and daily activities such as when blood pressure activity will rise and when the remaining blood pressure will drop. Laundry installations are workplaces where there is a physical hazard in the work process in the form of a hot working climate. In a hot working climate, the body regulates its temperature by accelerating the evaporation of sweat by widening (vasodilation) of blood vessels which results in increased blood circulation and increased capillaries accompanied by physiological responses, such as increased pulse and blood pressure. This study aims to analyze the relationship between the work of heat and blood pressure of workers in the Laundry Installation of RSUP Dr. Sardjito Yogyakarta. This study uses quantitative research design using a cross sectional approach. The population in this study were Laundry Installation workers with a sample of 35 respondents taken with total sampling. Data analysis using Chi-Square. The results showed that there was a relationship between the hot work climate and workers’ blood pressure (p = 0.03) and there was a relationship between the hot working climate and diastolic blood pressure of workers in the Laundry in RSUP Installation. Sardjito Yogyakarta (p = 0.01).